KETERAMPILAN BERBICARA MAHASISWA CALON GURU DALAM BERINTERTERAKSI DENGAN DOSEN - Sudarto, Sudarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is a survey research which aims to describe the speaking skills of the prospective teacher students in interacting with their lecturers. The subjects of this research were the prospective teacher students of PGSD FIP UNM who were actively in taking the part in lectures taught by researchers (Konsep Dasar IPA, Pendidikan IPA Lanjutan, Pengembangan Konsep Dasar IPA, dan Evaluasi Pembelajaran) whose parents' work backgrounds were farmers. The population in this study was of 100 people. The sampling method uses is a quota technique. The sample size was of 80 people, obtained using the Slovin formula. The data collection techniques used were a observation and interview techniques with research instruments in the form of observation sheets, daily recording sheets and interview guides. The data analysis technique used was the descriptive data analysis technique. Research results and conclusions: In general, the students in speaking when take interacting with their lecturers demonstrated the speaking skills of